SEMIOTICS STUDY ON CONNOTATIVE MEANING IN WORLD WILDLIFE FUND (WWF) ADVERTISING CAMPAIGN PUBLISHED UNDER THE ‘SAVE THE TIGER’ THEME - JEANITA, CHYNTIA AMELIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
There are three problems to be solved in this study, namely: (1) What signs are found in the World Wildlife Fund (WWF) advertisement published under “Save the Tiger” theme; (2) What meaning of the signs in the World Wildlife Fund (WWF) advertisement published under “Save the Tiger” theme are; and (3) How the signs support the idea of the World Wildlife Fund (WWF) advertising campaign.In this study the researcher uses the theory of Pierce to identify the sign employed in the advertisements and the theory connotation by Barthes to analyze the meaning behind the sign.Qualitative approach and document analysis are applied in this study. While, the data are six online World Wildlife Fund (WWF) advertisements published under the “Save the Tiger” theme.This study reveals that there are five topics about “Save the Tiger” that the researcher analyzes; they are illegal hunting, illegal souvenir, tiger extinction, tiger habitat loss and gathering help for the tiger. The researcher finds that there are 24 icons, 14 indexes and 17 symbols from 55 signs in total. The iconic sign is mostly used in all the advertisements. Furthermore, the researcher finds that each advertisement consists of several signs and each sign found in the advertisement has certain message related to the topic of the advertisement. Also, each sign has particular position either as the main sign or supporting sign. The main and supporting signs both have relation to strengthen the message.The researcher suggests the next researchers to conduct a study about semiotics by using another object and another theory to improve the understanding about semiotics.